METTL3 enhances dentinogenesis differentiation of dental pulp stem cells via increasing GDF6 and STC1 mRNA stability - Yue Pan; Ying Liu; Dixin Cui; Sihan Yu; Yachuan Zhou; Xin Zhou; Wei Du; Liwei Zheng; Mian Wan (BMC, 2023)
Abstract Background The dentinogenesis differentiation of dental pulp stem cells (DPSCs) is controlled by the spatio-temporal expression of differentiation related genes. RNA N6-methyladenosine (m6A) methylation, one of the most abundant internal epigenetic modification in mRNA, influences various events in RNA processing, stem cell pluripotency and differentiation. Methyltransferase like 3 (METTL3), one of the essential regulators, involves in the process of dentin formation and root development, while mechanism of METTL3-mediated RNA m6A methylation in DPSC dentinogenesis differentiation is still unclear. Methods Immunofluorescence staining and MeRIP-seq were performed to establish m6A modification profile in dentinogenesis differentiation. Lentivirus were used to knockdown or overexpression of METTL3. The dentinogenesis differentiation was analyzed by alkaline phosphatase, alizarin red staining and real time RT-PCR. RNA stability assay was determined by actinomycin D. A direct pulp capping model was established with rat molars to reveal the role of METTL3 in tertiary dentin formation. Results Dynamic characteristics of RNA m6A methylation in dentinogenesis differentiation were demonstrated by MeRIP-seq. Methyltransferases (METTL3 and METTL14) and demethylases (FTO and ALKBH5) were gradually up-regulated during dentinogenesis process. Methyltransferase METTL3 was selected for further study. Knockdown of METTL3 impaired the DPSCs dentinogenesis differentiation, and overexpression of METTL3 promoted the differentiation. METTL3-mediated m6A regulated the mRNA stabiliy of GDF6 and STC1. Furthermore, overexpression of METTL3 promoted tertiary dentin formation in direct pulp capping model. Conclusion The modification of m6A showed dynamic characteristics during DPSCs dentinogenesis differentiation. METTL3-mediated m6A regulated in dentinogenesis differentiation through affecting the mRNA stability of GDF6 and STC1. METTL3 overexpression promoted tertiary dentin formation in vitro, suggesting its promising application in vital pulp therapy (VPT).